Solvent-free semi-interpenetrating composite polymer electrolyte based on dual Li-salt for solid-state lithium batteries - Ghufira, .; Wu, Yi–Shiuan; Wu, She–Huang; Chang, Jeng-Kuei; Jose, Rajan; Yang, Chun-Chen (Elsevier Ltd, 2025)
All-solid-state lithium batteries are considered the most promising type of lithium batteries for achieving high energy density and safety. However, they suffer from challenges related to increasing the ionic conductivity, improving interfacial contact between the electrode and electrolyte, and suppressing the dendrite formation of lithium metal during charge-discharge cycles. In this work, a solid polymer electrolyte (SPE) was fabricated via a simple and fast method via ultraviolet (UV) curing to synthesize an all-solid-state polymer membrane with a semi-interpenetrating network. This solvent-free SPE was fabricated using poly (ethylene glycol) diacrylate, lithium bis(trifluoromethanesulfonyl)imide and lithium difluoro(oxalate)borate as salt with tetraethylene glycol dimethyl ether plasticizer. A commercial thin polyethylene separator was used to reinforce the dual-salt solid polymer electrolyte (DS-SPE). The DS-SPE has an average thickness, ionic conductivity, electrochemical stability window, activation energy (Ea), and transference number (tLi+) of ∼40 μm, 3.74 × 10−4 S cm−1 at 70 °C, 5.05 V at room temperature, 0.25 eV and 0.55, respectively. Our DS-SPE membrane achieved stable and uniform lithium stripping/plating in a symmetric cell for 600 h at 0.2 mA cm −2 and an areal capacity of 0.5 mAh cm −2 at 40 °C without short circuits. The Li/DS-SPE/LiFePO4 full cell demonstrated high stability with 100 % Coulombic efficiency and 94.20 % capacity retention at 1C rate after 100 cycles at 40 °C. The electrochemical performances of the cell based on our DS-SPE indicated that our novel DS-SPE is a promising candidate for solid-state lithium batteries applications.